Mechanistic Insights into LGALS3-Mediated Osteoarthritis Progression: Activation of the cGAS-STING Pathway as a Key Driver of Senescence-Related Osteoarthritis - Ruolan Wu; Tong Xiao; Zhen Chen; Qitao Yan; Ying Wang; Dingwei Peng; Jingli Chen; Ge Zeng (Journal of Pharmaceutical Innovation, 2026)

Exosomal PKM2 from AML cells reprograms endothelial metabolism to promote angiogenesis and chemoresistance - Xiaoting Wang; Ruolan You; Wenqi Fang; Lixia Kang; Danni Cai; Diyu Hou; Jingru Liu; Shuxia Zhang; Huifang Huang (Functional & Integrative Genomics, 2026)

Two-phase removal kinetics of antimicrobial resistance in collaborative composting: Thermophilic enhancement and rebound suppression - Ruonan Ma; Xuyan Li; Ruolan Tang; Yan Liu; Jiani Wang; Guoxue Li; Si Li; Shenzhong Tian; Tao Jiang; Jiali Chang; Jing Yuan (Bioresource Technology, 2026)

Mercury pollution remediation in paddy fields with biochar amendment - Yanxin Hu; Chuan Wang; Junyao Yan; Ruolan Li; Rasheed Mohammed Abdul; Yan An; Jinjuan Li; Ping Li (Applied Geochemistry, 2026)

Multi-media antibiotics, intracellular and extracellular antibiotic resistance genes in marine protected areas of the South China Sea: Spatiotemporal distribution and multi-factor drivers of dissemination - Chengcheng Bu; Limin Ma; Yu Hua; Shaopeng Xu; Yutong Zhang; Huadong Yi; Yuchen Han; Haoyu Zeng; Yongzhi Wang; Xiaoying Xu; Qihui Zhao; Ruolan Jia; et al. (Marine Pollution Bulletin, 2026)

Divergent aerosolization behaviors of bacteria and fungi shape the pathogen profile of pig manure composting-derived bioaerosols - Xia Gao; Jiani Wang; Lijuan Peng; Tianlong Song; Ruolan Tang; Yan Yang; Guoxue Li; Jing Yuan (Journal of Environmental Chemical Engineering, 2026)

Obtaining the thermal sensations of young children-cognitive theory-guided design and validation of thermal sensation measurements for preschool children - Yao Lu; Ruolan Zhou; Qian Kang; Hui Zhang; Yiqiang Xiao; Hankun Lin; Wei Lu; Lina Wang (Building and Environment, 2026)

Porcine epidemic diarrhea virus influences the expression of tight junction proteins through the polarity protein PAR6 - Tingyu Hu; Ruolan Zhang; Qian Weng; Simin Wang; Yuheng Li; Zhihua Pei; Kai Wang; Guixue Hu (Virus Genes, 2026)

Intercropping enhances aggregate stability on acidic red-soil slopes via an arbuscular mycorrhizal fungi-mediated glomalin-enzyme pathway - Ruolan Tang; Qirui Wang; Huahui Li; Xiongxing Pu; Wanting Li; Benshuai Yan; Ting Wang; Zilin Wang; Maopan Fang; Xinyue Li; Yongmei Li; Jixia Zhao (Applied Soil Ecology, 2026)

Machine learning based accurate storm surge peak and timing forecast in Pearl River Estuary - Ruolan Xiong; Xiaohui Wang; Fuhai Dao; Hongze Leng; Junqiang Song (Frontiers in Marine Science, 2026)
With climate warming, storm surge increasingly threatens coastal cities, underscoring the necessity for accurate and timely forecasts of peak surge height and timing. Among widely used neural network-based approaches in storm surge forecasting, the Gated Recurrent Unit (GRU), while strong in sequential prediction, tends to underestimate peak magnitudes and exhibits timing errors at extended lead times. To address the issue, this study developed a single-station GRU prediction model using storm surge data from 42 tropical cyclones (2000-2023) at nine stations in the Pearl River Estuary. To reduce peak underestimation, an iterative forecasting scheme was designed, incorporating tropical cyclone (TC) parameters selected via Accumulated Local Effects (ALE) and correlation coefficient. To mitigate peak timing errors, a Support Vector Regression (SVR) model based on TC peak intensity elements was proposed to predict and correct peak timing errors. Additionally, multi-station joint forecasting was explored by embedding spatial information between stations and TC tracks. Results based on leave−one−out cross−validation (LOOCV) indicated that integrating TC location, distance, and 34−kt wind radii in the key quadrants yielded a 27% reduction in Peak Error (PE) at 12–18 h and a 13% reduction in RMSE over 1–18 h for the 35 test cases. After applying the SVR−based phase correction, the forecast for all cases achieved an 55% reduction in Timing Error (TE) and a 2.81% reduction in RMSE relative to the uncorrected forecast. Compared to numerical model outputs, the RMSE of water level sequence during Typhoon Hato was decreased by 0.22 m. Multi-station joint forecast results showed that embedding such spatial information not only enhances forecast skill across multiple gauges but also provides benefits for stations with sparse historical data. This study offers a promising method that targets both the magnitude and timing of storm surge peaks, thereby improving the accuracy and reliability of storm surge forecasting.

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Multi-media distribution, source apportionment, and risk assessment of legacy and current-use organophosphorus pesticides in typical agricultural watersheds of China - Chengcheng Bu; Limin Ma; Weiwei Zhang; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Qi Wang; Yuefei Ruan; Chong Chen (Water Research, 2026)

Exceptional methylmercury bioaccumulation in rice grain from karst region with high geological background - Langfei Wei; Shaochen Yang; Ruolan Li; Rasheed Mohammed Abdul; Yanxin Hu; Haiyu Yan; Baolin Wang; Haiyan Hu; Ping Li (Applied Geochemistry, 2026)

Stratified layering for soil profile: Dynamic short field Mamba network - Shaohua Zeng; Zhihao Chen; Ruolan Zeng; Shuai Wang; Yang Wang (Computers and Electronics in Agriculture, 2026)

Mechanistic differences in ce-MoS2 catalytic activation of peroxides: Pathway divergence and reactive species roles - Shuyun Tai; Lei Sun; Yuxin Wang; Ruolan Huang; Yang Yang; Yu Chen; Hong Chang (Journal of Hazardous Materials, 2025)

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Hierarchical sulfur vacancy engineering via lattice strain for commercial-grade photocatalytic H2O2 generation in Sm3+-doped ZnIn2S4 - Ruolan Zhao; Chen Chen; Yachao Xu; Yue Qu; Peng Yu; Ying Wang (Chemical Engineering Journal, 2025)

Defect-engineered Z-scheme BiOBr/TiO2 heterojunctions with interfacial potential wells for selective CO2 photoreduction - Shijie Liu; Ruolan Zhao; Yachao Xu; Maoxiang Li; Zihan Ma; Xin Chang; Ying Wang; Mingyi Zhang (Chemical Engineering Journal, 2025)

Optimizing organic waste co-composting: Component ratio thresholds for dual enhancement of maturity and gaseous emission reduction - Ruonan Ma; Ruolan Tang; Guannan Zheng; Jiani Wang; Zhongliang Cui; Yan Liu; Guoxue Li; Fanqiao Meng; Jing Yuan (Journal of Environmental Chemical Engineering, 2025)

Response of maturity, humification, and gaseous emissions to initial moisture content in collaborative composting of multiple organic solid wastes - Xuyan Li; Jiacong Lin; Ruolan Tang; Yan Liu; Jiani Wang; Guoxue Li; Jing Yuan; Ruonan Ma (Journal of Environmental Chemical Engineering, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Black phosphorus-doped Janus structured electrospun fibrous membrane with antibacterial properties for wound healing - Ruolan Du; Xinyu Li; Wenbo Wu; Jingxin Zhou; Zhiwei Liu; Yuehua Wang; Tifeng Jiao (Chemical Engineering Journal, 2025)

The effect of probiotics supplementation on cancer-treatment complications: a critical umbrella review of interventional meta-analyses - Zhao Yang; Shijie Zhang; Lu Ying; Wenjing Zhang; Xiaoyang Chen; Youfeng Liang; Ruolan Chen; Keying Yao; Chunhui Li; Changyuan Yu; Parmida Jamilian; Meysam Zarezadeh; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Examination of green roofs' cooling effects in a big city based on multi-source remote sensing data: An example from central Xi’an, China - Xiya Yan; Jianhong Liu; Wei Zhang; Ziqi Wang; Ruolan Jia; Lei Wang; Nan Liu; Yu Zhu (Sustainable Cities and Society, 2025)

Visual perception for long-distance and small target detection in autonomous maritime navigation - Ruolan Zhang; Xingchen Ji; Sean Loughney; Jin Wang; Zaili Yang (Ocean Engineering, 2025)

Transport and transformation of colloidal and particulate mercury in contaminated watershed - Junyao Yan; Ruolan Li; Chuan Wang; Shaochen Yang; Mingyu Shao; Leiming Zhang; Ping Li; Xinbin Feng (Water Research, 2025)

Preparation of ZnWO4/Bi4O5I2 composite photocatalyst and study of its antibacterial properties - Ling Zhang; Zixin Wang; Ruolan Wei; Tengyuan Gao; Jingmei Li; Luyin Zhao; Deming Han; Xiulong Li (Journal of Water Process Engineering, 2025)

Mapping cropland use changes in the Guanzhong Plain of China based on a two-level classification framework - Wei Zhang; Jianhong Liu; Ruolan Jia; Xi Wang; Xiya Yan; Ziqi Wang; Jing Wang; Wei Li; Peijun Sun (International Journal of Remote Sensing, 2025)

SQSTM1/p62 predicts prognosis and upregulates the transcription of CCND1 to promote proliferation in mantle cell lymphoma - Shuxia Zhang; Feichao Huang; Jin Wang; Ruolan You; Qiqi Huang; Yuanzhong Chen (Protoplasma, 2025)

Comparative chloroplast genome analysis of the medicinal species in Rubus: Insights into genomic characterization and phylogenetic relationships - Jiayu Jiang; Rui Tian; Ruolan Wang; Shuang Wang; Dequan Zhang (Plant Systematics and Evolution, 2025)

Identification and Removal of Light Pollution in Maritime Night-Time Images Based on Spatial Frequency Blocks - Hui Sun; Jingyang Wang; Mingyang Pan; Zongying Liu; Shaoxi Li; Ruolan Zhang; Yang Wei (Journal of Marine Science and Engineering, 2025)
The safety of ships during nighttime navigation has always been a major concern. With the widespread application of technologies such as intelligent recognition, intelligent detection, and unmanned ship navigation at night, nighttime maritime light pollution has significantly affected the effectiveness of these intelligent technologies and navigation safety. Therefore, effectively eliminating nighttime maritime light pollution has become an urgent challenge that needs to be addressed. This paper presents a model based on spatial frequency blocks (SFBs) to solve the problem of light pollution in nighttime sea images. The model includes ResNet-50, an encoder, a decoder, and a discriminator. To enable the model to better remove the influence of light pollution, this study designs a method of first detecting the light pollution area and then removing it. It extracts image information from the space–frequency domain to help eliminate light pollution and retain more image information. The experimental results show that on the nighttime light pollution dataset, the Peak Signal-to-Noise Ratio (PSNR) of the model is improved to 24.91 compared to the current state-of-the-art image restoration model, while the Frechet inception distance (FID) is reduced to 64.85. At the same time, in the real night environment, the model can better remove light pollution to recover the original nighttime information. It has excellent performance and provides a certain reference value for advancing the safety of nighttime maritime navigation.

Bioaerosol emission characteristics and potential risks during composting: Focus on pathogens and antimicrobial resistance - Ruonan Ma; Lijuan Peng; Ruolan Tang; Tao Jiang; Jiali Chang; Guoxue Li; Jiani Wang; Yan Yang; Jing Yuan (Journal of Hazardous Materials, 2025)

Correlation analysis and modeling application from objective indicators to subjective evaluation of scented tea: A case study of rose tea - Ruolan Song; Meng Shen; Yanran Wang; Youyi Sun; Jiamu Ma; Qingyue Deng; Xueyang Ren; Xianxian Li; Yuan Zheng; Yingyu He; Feng Zhang; Mingxia Li; et al. (Food Chemistry, 2025)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Microwave pyrolysis of Choerospondias axillaris seeds with their derived biochar for comprehensive utilization of the biomass - Ruolan Zhou; Xiaojie Tian; Xiaofei Wang; Yuan Zeng; Linyao Ke; Qiuhao Wu; Rui Liao; Roger Ruan; Liangliang Fan; Yunpu Wang (Chemical Engineering Journal, 2024)

Ground visibility prediction using tree-based and random-forest machine learning algorithm: Comparative study based on atmospheric pollution and atmospheric boundary layer data - Fuzeng Wang; Ruolan Liu; Hao Yan; Duanyang Liu; Lin Han; Shujie Yuan (Atmospheric Pollution Research, 2024)

Mercury sources, transport, and transformation in rainfall-runoff processes: Mercury isotope approach - Ruolan Li; Junyao Yan; Chuan Wang; Shaochen Yang; Lin Zhang; Tao Peng; Wei Zhu; Ping Li; Leiming Zhang; Xinbin Feng (Water Research, 2024)

Dicyandiamide addition delay nitrous oxide emission and shift its production pathway from denitrification to incomplete nitrification in maturation phase of composting - Yan Liu; Ruolan Tang; Guoliang Liu; Guoxue Li; Jiani Wang; Yu Cai; Yilin Kong; Jing Yuan (Chemical Engineering Journal, 2024)

Rapid and highly sensitive colorimetric LAMP assay and integrated device for visual detection of monkeypox virus - Yadan Peng; Ruolan Hu; Shuang Xue; Yugan He; Lili Tian; Zehan Pang; Yile He; Yuqi Dong; Yinghan Shi; Shuqi Wang; Bixia Hong; Ke Liu; et al. (Analytica Chimica Acta, 2024)

Ferroptosis is involved in trophoblast cells cytotoxicity induced by black phosphorus nanoparticles - Ruolan You; Yaming Mu; Jiaqi Zhou; Chunying Wang; Zhenya Fang; Yu Liu; Shiyu Liu; Qingfeng Zhai; Changqing Zhang (Toxicology, 2024)

Pickering emulsion stabilized using modified gluten protein - Yongling Song; Yuanyuan Hou; Siqi Ren; Chenling Qu; Miao Li; Yanlin Tu; Ruolan Wang (Journal of Food Engineering, 2024)

Production of monocyclic aromatic hydrocarbons from microwave co-pyrolysis of polyethylene terephthalate and low-density polyethylene using coconut husk carbon as microwave absorbent - Xiaofei Wang; Yujie Peng; Ruolan Zhou; Liangliang Fan; Qi Zhang; Xian Cui; Qiuhao Wu; Yuan Zeng; Xiaojie Tian; Linyao Ke; Roger Ruan; Yunpu Wang (Chemical Engineering Journal, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

Response of organic aerosol in Beijing to emission reductions during the XXIV Olympic Winter Games - Qipeng Qu; Shuxiao Wang; Bin Zhao; Ruolan Hu; Chengrui Liang; Haowen Zhang; Shengyue Li; Boyang Feng; Xuan Hou; Dejia Yin; Jinhong Du; Yangxi Chu; et al. (Science of The Total Environment, 2024)

Incorporating edible oil during cooking tailors the microstructure and quality features of brown rice following heat moisture treatment - Yabin Guo; Ruolan Fang; Zhuoting Wu; Gaolei Xi; Dongling Qiao; Genfa Wang; Ting Cui; Liang Zhang; Siming Zhao; Binjia Zhang (Food Research International, 2024)

Interaction of high amylose corn starch with polyphenols: Modulating the stability of polyphenols with different structure against thermal processing - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Chemistry, 2024)

Study on the improvement of complexation efficiency and anti-digestibility of phenolic acids based on electrospun starch fibers - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yanhong Bi; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2024)

Rice bran peptide with α-glucosidase inhibition activity: Preparation, evaluation and molecular mechanism - Weiwei Liu; Ruolan Ma; Gengjie Cui; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Journal of Cereal Science, 2024)

Low transplacental transfer of PFASs in the small-for-gestational-age (SGA) new-borns: Evidence from a Chinese birth cohort - Yijun Fan; Liyan Guo; Ruolan Wang; Jingjing Xu; Yuanyuan Fang; Wenxin Wang; Jia Lv; Weitian Tang; Hua Wang; De-Xiang Xu; Lin Tao; Yichao Huang (Chemosphere, 2023)

Chemometrics-based investigation of non-volatiles/volatiles flavor of tencha (Camellia sinensis cv. Yabukita, Longjing 43 and Baiye 1) - Qiuwen Yu; Chuangsheng Huang; Ruolan Zhu; Debiao Lu; Liping Liu; Jianhong Lai; Xinyao Zhong; Jueshan Guan; Senjie Zhou; Yilin Tong; Zipei Wang; Ping Chen; et al. (Food Research International, 2023)

Downregulation of ITGA5 inhibits lymphangiogenesis and cell migration and invasion in male laryngeal squamous cell carcinoma - Xiaoting Wang; Jun Huang; Ruolan You; Diyu Hou; Jingru Liu; Long Wu; Meihong Yao; Fuwen Yang; Huifang Huang (Protoplasma, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

A critical review on the thermal management of data center for local hotspot elimination - Ruolan Zhao; Yahui Du; Xiaochen Yang; Zhihua Zhou; Wufan Wang; Xueqing Yang (Energy and Buildings, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

A global meta-analysis of greenhouse gas emissions and carbon and nitrogen losses during livestock manure composting: Influencing factors and mitigation strategies - Yan Liu; Ruolan Tang; Liqiong Li; Guannan Zheng; Jiani Wang; Guoying Wang; Ziyang Bao; Ziming Yin; Guoxue Li; Jing Yuan (Science of The Total Environment, 2023)

Temporal succession and spatial heterogeneity of humification, pathogens and bacterial community in facultative heap composting - Yan Yang; Yilin Kong; Guoying Wang; Yujun Shen; Ruolan Tang; Ziming Yin; Jia Yang; Guoxue Li; Jing Yuan (Process Safety and Environmental Protection, 2023)

Preparation and application of cinnamon-Litsea cubeba compound essential oil microcapsules for peanut kernel postharvest storage - Haoxin Lv; Shanshan Huo; Lingli Zhao; Hanxiao Zhang; Yijun Liu; Shichang Liu; Akio Tani; Ruolan Wang (Food Chemistry, 2023)

Heavy metals in fish, rice, and human hair and health risk assessment in Wuhan city, central China - Muhammad Ubaid Ali; Chuan Wang; Yuan Li; Ruolan Li; Shaochen Yang; Li Ding; Lin Feng; Bo Wang; Ping Li; Ming Hung Wong (Environmental Pollution, 2023)

Impact of battery electric vehicles on ventilation design for road tunnels: A review - Xu Wang; Mingnian Wang; Ruolan Jiang; Jiani Xu; Bingtian Li; Xiao Wang; Mingyu Lei; Pengfei Su; Chaopeng Liu; Qianru Yang; Jianle Yu (Tunnelling and Underground Space Technology, 2023)

Molecular tracers, mass spectral tracers and oxidation of organic aerosols emitted from cooking and fossil fuel burning sources - Chengrui Liang; Shuxiao Wang; Ruolan Hu; Guanghan Huang; Jinzi Xie; Bin Zhao; Yuyang Li; Wenfei Zhu; Song Guo; Jingkun Jiang; Jiming Hao (Science of The Total Environment, 2023)

Effects of radon exposure on gut microbiota and its metabolites short-chain fatty acids in mice - Huimeng Liu; Meiyu Wang; Guangrui Chen; Huiyu Zhou; Jiahui Dong; Lei Yang; Tong Li; Zhiyun Meng; Ruolan Gu; Hui Gan; Zhuona Wu; Shuchen Liu; et al. (Toxicology, 2023)

Mercury migration to surface water from remediated mine waste and impacts of rainfall in a karst area – Evidence from Hg isotopes - Junyao Yan; Ruolan Li; Muhammad Ubaid Ali; Chuan Wang; Bo Wang; Xingang Jin; Mingyu Shao; Ping Li; Leiming Zhang; Xinbin Feng (Water Research, 2023)

Effect of moisture content, aeration rate, and C/N on maturity and gaseous emissions during kitchen waste rapid composting - Ruolan Tang; Yan Liu; Ruonan Ma; Lanxia Zhang; Yanming Li; Guoxue Li; Dingmei Wang; Jiacong Lin; Qinfen Li; Jing Yuan (Journal of Environmental Management, 2023)

Evaluation and Hydrological Application of CMADS Reanalysis Precipitation Data against Four Satellite Precipitation Products in the Upper Huaihe River Basin, China - Shanhu Jiang; Ruolan Liu; Liliang Ren; Menghao Wang; Junchao Shi; Feng Zhong; Zheng Duan (Journal of Meteorological Research, 2020)

HIF-1α/Beclin1-Mediated Autophagy Is Involved in Neuroprotection Induced by Hypoxic Preconditioning - Na Lu; Xingxing Li; Ruolan Tan; Jing An; Zhenlu Cai; Xiaoxuan Hu; Feidi Wang; Haoruo Wang; Chengbiao Lu; Haixia Lu (Journal of Molecular Neuroscience, 2018)